Sensorless control of surface mounted permanent magnet machine using fundamental PWM excitation - Hua, Yahan (2009)
This thesis describes the development of a sensorless control method for a surface mounted permanent magnet synchronous machine drive system. The saturation saliency in the machine is tracked from the stator current transient response to the fundamental space vector PWM (pulse width modulation) excitation. The rotor position and speed signals are obtained from measurements of the stator current derivative during the voltage vectors contained in the normal fundamental PWM sequence.